Perancangan sistem E-Learning berbasis website untuk mendukung pembelajaran di SDN kalaki - Wahyuni, Wenti Ayu; Fahrurrazikin, Fahrurrazikin; Zaeniah, Zaeniah (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2025)
Technology plays a significant role in enhancing the quality of education, especially in remote areas such as SDN Kalaki. This school faces challenges like inadequate infrastructure and distractions from non-academic activities, such as horse racing, which divert students' focus from education. This study aims to design and develop a web-based e-learning information system accessible to students and teachers from various locations. The system is designed to improve teacher-student interaction and increase learning interest. The research employs a prototyping approach, involving interviews, observations, and iterative development. The results indicate that the developed e-learning system effectively enhances the efficiency of the learning process and provides a relevant solution to the limitations of educational access in the region.